The politics of nationalism and white racism in the UK - Flemmen, Magne (The British journal of sociology, 2017)
This paper considers the contemporary significance of white racism and its association with nationalist sentiment amongst a cohort late middle aged white Britons, using survey responses and qualitative interviews from the 1958 National Child Development Study. We have shown that although overt racism is very limited, a substantial minority of white Britons display ambivalent feelings which have the potential to be mobilised in racist directions. We argue against the view that disadvantaged white working class respondents are especially xenophobic, and show that racist views are not strongly associated with social position. In exploring the clustering of different nationalist and racist sentiments amongst economic and cultural elites, and comparing these with ‘disenfranchised’ respondents with little economic and cultural capital, we show that it is actually the elite who are most likely to articulate ‘imperial racism’. By contrast, the ‘disenfranchised’ articulate a kind of anti‐establishment nationalism which is not strongly racist. We also show that the elite are strongly internally divided, with a substantial number of the cultural elite being strongly anti‐racist and committed to multi‐culturalism, so generating strong internal factionalism between elite positions. Our paper therefore underscores how intensifying inequalities have facilitated the volatility and variability of nationalist and racist sentiment.